TINJAUAN YURIDIS PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA NOMOR 10 TAHUN 2020 TENTANG SYARAT PEMBERIAN ASIMILASI DAN HAK INTEGRASI BAGI NARAPIDANA DAN ANAK DALAM RANGKA PENCEGAHAN DAN PENANGGULANGAN PENYEBARAN COVID-19 DALAM PERSPEKTIF HAK ASASI MANUSIA (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Legal protection for prisoners can be interpreted as an effort to protect the law against various freedoms and human rights, as well as various interests related to legal protection of prisoners. Understanding the foregoing, it can be concluded that the Standard Minimum Rules (SMR) which are the result of the first United Nations (UN) Congress on Crime Prevention and the treatment of lawbreakers, are very important in ensuring the rights of prisoners. As a result of the impact of the Covid-19 Pandemic which hit the world, especially Indonesia, it is very important for the government to take a stance considering the conditions of prisons have been overcrowded. So that the Minister of Law and Human Rights gave birth to a policy in the form of Ministerial Regulation of Law and Human Rights Number 10 of 2020, to provide assimilation and integration rights that conditional release of approximately 30,000 more prisoners. The objectives of writing this thesis are: First, to find out a juridical review of the Regulation of the Minister of Law and Human Rights Number 10 of 2020 concerning the Terms of Providing Assimilation and Integration Rights for Prisoners and Children in the Context of Preventing and Combating the Spread of Covid-19 in a Human Rights Perspective. Second, to find out the urgency of the formation of Minister of Law and Human Rights Regulation Number 10 of 2020. This research is a normative legal research. This is based on literature research that takes quotations from reading books, or supporting books that are related to the problem to be studied. This study uses data sources in the form of secondary data sources consisting of primary, secondary or tertiary legal materials. This study also uses qualitative data analysis and produces descriptive data. From the results of the research conducted, there are several conclusions obtained, namely: First, the Ministry of Law and Human Rights takes steps to save prisoners and children in prisons, where prisoners need the right to survive and get health in conditions during the Covid-19 pandemic. Second, the policies created by the Government are appropriate and hierarchically in accordance with the prevailing legislative framework. This regulation is very necessary considering health emergencies and conditions of prisons that are vulnerable to the Covid-19 pandemic. It is hoped that in the future the people in Indonesia will help each other in conditions outside of correctional institutions as regulated in the Regulation of the Minister of Law and Human Rights Number 10 of 2020 concerning the Conditions for Providing Assimilation and Integration Rights for Prisoners and Children in the Context of Preventing and Combating the Spread of Covid-19 . Keywords: Human Rights Assimilation-Integration-Covid-19-Human Rights